(Ine)quality in Healthcare: a perspective from the accreditation of clinical laboratories in Costa Rica - Quesada-Yamasaki, Daniel; Zeledón-Mayorga, Raúl (Población y Salud en Mesoamérica, 2021)
Introduction: Given the relevance of quality-assured laboratory services for health system strengthening and improvement, this study had the objective of exploring the distribution of ISO 15189-accredited and non-accredited laboratories in Costa Rica, in order to identify possible gaps in the fulfillment of its commitment to provide ‘quality healthcare for all’. Methods: Our research was conducted with a descriptive scope and following a quantitative approach. Costa Rica’s Accreditation Body and College of Microbiologists databases were searched to collect data regarding clinical laboratory registration and ISO 15189 accreditation status. Laboratory availability indicators by geographical division were computed with this data. Results: Out of 480 clinical laboratories allowed to operate in Costa Rica as of January 2021, only 5 (about 1%) have been accredited in compliance with ISO 15189, all of which are private and located in the province of San José. Also, laboratory density (in terms of facilities per 100 km2 and per 100 000 population) is heterogeneous among provinces. Clinical laboratory services are more easily available in ‘central’ provinces of the country (e.g. San José and Heredia), where ratios for laboratory density are higher. On the contrary, coastal provinces such as Limón and Puntarenas exhibit low laboratory density ratios, reflecting geographical disparities in access to healthcare. Conclusions: Geographic disparities in the access to clinical laboratory services were observed. This should raise awareness among public health authorities and private healthcare providers regarding the country’s progress in attaining its ‘quality healthcare for all’ commitment.